New logistics paradigms in Poland - Elżbieta Gołembska (Logistics, 2019)
This article presents the results of theoretical and empirical studies on the search for new logistics development paradigms needed to meet the challenges of the twenty-first century global economy. The author reviews the major factors determining the effectiveness of international processes and operations, including logistics success potentials in supply chains. Furthermore, the article proposes methods for measuring logistics performance, specifically the logit model and the model of fuzzy logic, which could be used to assess whether a firm's planned investments in logistics infrastructure will end in success or failure. The article also evaluates the impact of logistics on the development of international trade in the practice of Polish firms. The studies cover a period before Poland's accession to the European Union (EU) (2000 to 2004), and after the accession, from 2005 to 2016, and are supplemented with a forecast for logistics development in Polish firms until 2020.
Keywords: 650; international business; logistics paradigms; logit model; strategic alliances; the practice of logistics in Poland